Influence of varying sheet material properties on dry deep drawing process - Krachenfels, Kim; Rothammer, Benedict; Zhao, Rong; Tremmel, Stephan; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2019)
Deep drawing is one of the most important processes in sheet metal forming. Conventionally, lubricants are used to reduce friction and wear. Demands for increased sustainability, environmental protection and resource efficiency motivate the realization of lubricant-free forming processes. The direct contact between tool and workpiece during dry deep drawing results in changed tribological conditions, which cause an increase in friction and wear. Friction-reducing surface modifications of the tool such as carbon based coatings are being developed for the adaptation of the tribological conditions. The aim of this work is the simulation-based analysis of the stress spectrum for varying sheet properties for the qualification of wear-reducing surface modifications for a wide range of applications. By a simulation model for a rectangular cup, the influence of different batches of steel and aluminum materials with varying friction coefficients and mechanical properties is investigated within the framework of variant simulations. The tribological conditions in the simulation are described on the basis of friction coefficients from the strip drawing test. From the simulation results, the applicability of surface modifications for dry deep drawing is being evaluated depending on the sheet specific properties.<br